2009
DOI: 10.1016/j.brainres.2009.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen activator inhibitor type 1 derived peptide, EEIIMD, diminishes cortical infarct but fails to improve neurological function in aged rats following middle cerebral artery occlusion

Abstract: Age is a primary risk factor in stroke that is often overlooked in animal studies. We contend that using aged animals yields insight into aspects of stroke injury and recovery that are masked, or not elicited, in younger animals. In this study, we examined effects of co-administration of a plasminogen activator inhibitor type 1 derived peptide, EEIIMD, with tissue plasminogen activator (tPA) on infarct volume and functional outcome in aged rats following a transient middle cerebral artery occlusion. Results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
21
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 38 publications
(41 reference statements)
8
21
0
Order By: Relevance
“…This finding is also consistent with previous studies showing larger infarct volumes and less functional recovery in aged mice (DiNapoli et al, 2008; Dinapoli et al, 2006; Dong et al, 2014; Rosen et al, 2005; Tan et al, 2009). We found that the striatum was especially affected in the aged animals after stroke.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is also consistent with previous studies showing larger infarct volumes and less functional recovery in aged mice (DiNapoli et al, 2008; Dinapoli et al, 2006; Dong et al, 2014; Rosen et al, 2005; Tan et al, 2009). We found that the striatum was especially affected in the aged animals after stroke.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, 1 recent study has shown that coadministration of a plasminogen activator inhibitor type 1-derived peptide, EEIIMD, with tissue plasminogen activator, a drug currently used for thrombolysis in stroke units, produced no improvement in total infarct volume, edema formation, or functional outcome in aged rats. 14 Improvement of function under treatment may suggest a direct effect of G-CSF on recovery of motor function and may be similar to our recent findings showing that G-CSF is an essential factor for the development of normal running function in wild-type and G-CSF Ϫ/Ϫ mice. 9 Potential mechanisms include a relative shift in favor of activation (upregulation of NMDA receptors, downregulation of GABA receptors) and improved behavioral performance associated with G-CSF stimulation.…”
Section: Discussionsupporting
confidence: 90%
“…The protective effect of r-tPA over placebo (saline) was lost at 6 h following ischemic stroke. The main finding of this study, taking into account prior findings demonstrating a protective effect of r-tPA when administered at 2 hours after ischemic stroke (DiNapoli et al ., 2008; Tan et a l., 2009), was that r-tPA in combination with the recombinant human apyrase (APT102) safely extended the time window for r-tPA out to 6 h after ischemic stroke in aged female rats. This study showed that co-administration of APT102 with r-tPA significantly reduced mortality rate, decreased infarct volume and cerebral hemorrhage, and improved neurological functional outcome at 24 h following MCAO as compared to subjects treated with r-tPA alone.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were given a reversible embolic MCAO as previously described (Dinapoli et al, 2006; DiNapoli et al, 2008; Tan et al, 2009). Briefly, rats were anesthetized with 2% isoflurane in a mixture of 30% oxygen and 70% nitrous oxide.…”
Section: Methodsmentioning
confidence: 99%